The teacher as a reflective researcher: debate on his/her educational practice development (Olhar de Professor, 2012)
This article aims to analyze the necessity of practical training for teacher-as-refl ectiveresearchers. In particular, it refl ects on the process of teaching practice, both in terms of technical rationality and the epistemology of practice. It assumes that teaching practice is based on a continuous dialogue with other sciences. Refl ection, research and teaching are constantly being problematized and (re)constructed through investigative teaching praxis, as they help to (re)think and (re)construct the complexity of life, that is, of text-context. From this standpoint, on the one hand educating is above all about deconstructing technical rationality and on the other hand it is about constructing the epistemology of investigative praxis of the teacher. Furthermore, it is also about being indignant and intervening in the world to transform it and make it more equal and humane.
Keywords: Researcher teacher. Refl ective practice. Development.